Análise do escoamento de HFC-134a em tubos capilares usando o modelo de dois fluidos - Seixlack, Andre Luiz [UNESP]; Prata, Alvaro Torebes; Melo, Cláudio (My University, 1996)
This work presents a numerical model to simulate refrigerant flow through capillary tubes, commonly used as expansion devices in refrigeration systems. The capillary tube is considered straight and horizontal. The flow is taken as one-dimensional and adiabatic. Steady state and thermodynamic equilibrium conditions are assumed. The two-fluid model, involving four conservation equations and considering the hidrodynamic nonequilibrium between the liquid and vapor phases is applied to the flow region. The pressure profiles and the mass flow rates given by the model are compared with experimental data.
Analysis of the HFC-134a refrigerant flow through capillary tubes using the two-fluid model
Keywords: Flow Through Capillary Tubes; HFC-134a; Refrigerant Fluid; Two-Fluid Model; Capillary tubes; Computer simulation; Fluorocarbons; Mass transfer; Mathematical models; Phase equilibria; Pressure; Refrigerants; Refrigeration; Thermodynamics; Conservation equation; Expansion devices; Mass flow rates; Refrigerant flow; Thermodynamic equilibrium; Two fluid model; Pipe flow